Style and the nineteenth-century British critic : sincere mannerisms - Camlot, Jason, 1967- (Nineteenth century (Aldershot, England), 2008)
In analyzing the nonfiction works of writers such as John Wilson, J.S. Mill, De Quincy, Ruskin, Arnold, Pater, and Wilde, Jason Camlot provides an important context for the nineteenth-century critics' changing ideas about style, rhetoric, and technologies of communication. In particular, Camlot shows how new print media affected the Romantic and Victorian critic's sense of self, and how the figure of the professional critic soon subsumed the authority of the polyglot intellectual.